From catwalk to kitchen: A qualitative study of luxury fashion companies’ diversification into hospitality and restaurant sector - Simone Luongo; Fabiana Sepe; Elena Lupolo; Giovanna Del Gaudio (PLoS ONE, 2026)
This study examines the strategic diversification of luxury fashion brands into the hospitality and restaurant industry, with a particular focus on sustainability. The objective is to explore the motivations behind this cross-industry expansion, the strategies employed and the sustainable practices integrated into such ventures. A qualitative research design is applied, drawing on semi-structured interviews with stakeholders from leading luxury fashion companies. This approach allows for an in-depth understanding of how experiential branding, strategic decision-making and sustainability are embedded within hospitality initiatives. The findings reveal that luxury brands enter the hospitality sector to enrich the brand experience, strengthen customer engagement and foster innovation in sustainability. Sustainable practices are identified both in operational management and in customer-facing activities, though the extent of integration varied across cases. The results underscore the dynamic relationship between experiential branding and sustainability, highlighting opportunities for competitive differentiation as well as challenges in aligning brand identity with new industry practices. This research contributes to the growing literature on luxury brand management and diversification by demonstrating how sustainability influences experiential strategies in cross-industry contexts. The originality of this paper lies in its integrated view of luxury branding, diversification and sustainability, showing how fashion companies leverage hospitality ventures to reinforce brand value and connect with socially conscious consumers.